POLICY IMPLEMENTATION OF THE SABILILLAH SPECTACULAR STAGE (SSS) PROGRAM TO INCREASE STUDENTS’ SPEAKING SKILLS - Mamnunah Mamnunah; Syihabuddin Syihabuddin; Yayan Nurbayan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
One of the factors that support and influence students' fluency in Arabic communication is the presence of a language-learning environment (bi'ah lughawiyah). This study aimed to describe how Pesantren Sabilillah implemented the policies in the Sabilillah Spectacular Stage program in improving Maharatul Kalam and how the program improved students’ speaking skills (maharah al-kalam). This study used a qualitative approach. The data were obtained from interviews, observations, and documentation. Participants included the boarding school caretakers, the Arabic language program coordinator, asatidz and ustadzat, and all students living in the boarding school dormitory. This study's results indicate that the Spectacular Stage policies include formulating objectives in the Sabilillah Spectacular Stage program and the timing of the program. Meanwhile, the implementation of this policy includes the policy of grouping students, the formation of the Katibah al-Mukhalifah group, Taqdim al-Mufradat, and Tadrib al-Barnamij.